Pengaruh Pertumbuhan Ekonomi, Inflasi dan BI Rate terhadap LDR (Loan to Deposit Ratio) di Indonesia - Tony Yanuar Syahputra; Yenny Kornitasari (Journal of Regional Economics Indonesia, 2022)
This study aims to examine the effect of economic growth, inflation and the BI Rate on the LDR (Loan to Deposit Ratio) in Indonesia. The author uses LDR as the dependent variable and includes the variables of economic growth, inflation, BI Rate, net interest income, and operating costs on operating income as independent variables. In this case, the method of writing multiple linear regression uses the OLS and ECM models for the 2016-2020 period. The results of the study show that: (i) the variable economic growth has a positive and significant effect on LDR in Indonesia; (ii) inflation variable has a negative and insignificant effect on LDR in Indonesia; (iii) the BI Rate variable has a positive and significant effect on LDR; (iv) the variable net interest income has a positive and significant effect on LDR; and (v) for the variable operating costs on operating income has a positive and significant effect on LDR in Indonesia